Rapid isolation, reliable characterization, and water solubility improvement of polymethoxyflavones from cold‐pressed mandarin essential oil. Issue 11 (6th May 2016) - Russo, Marina; Rigano, Francesca; Arigò, Adriana; Sciarrone, Danilo; Calabrò, Maria Luisa; Farnetti, Sara; Dugo, Paola; Mondello, Luigi
Abstract : Polymethoxyflavones possess many biological properties, as lipid‐lowering, hypoglycaemic, anti‐inflammatory, antioxidant, and anticancer activities, therefore, they may be employed as nutraceuticals or therapeutic agents. The scarcity of pure polymethoxyflavones on the market as well as their low water solubility limited in vivo studies and the use of polymethoxyflavones as food or pharmaceutical supplements. Since mandarin peels are a rich source of polymethoxyflavones, tangeretin, nobiletin, sinensetin, tetra‐ O ‐methyl scutellarein, and heptamethoxyflavone were purified from a nonvolatile residue of a cold‐pressed mandarin essential oil using a multidimensional preparative liquid chromatographic system coupled with a photodiode array detector and a single quadrupole mass spectrometer. A new prototype, consisting of a nano‐liquid chromatography system coupled with an electron ionization mass spectrometer, was used for the characterization of the pure isolated molecules. Finally, due to the collection of highly pure nobiletin and tangeretin, the ability of 2‐hydroxypropyl‐β‐cyclodextrin to enhance the water solubility of both polymethoxyflavones was evaluated by phase solubility studies and Job's plot method.